2022
DOI: 10.3390/ijerph19095307
|View full text |Cite
|
Sign up to set email alerts
|

Type of Findings Generated by the Occupational Therapy Workforce Research Worldwide: Scoping Review and Content Analysis

Abstract: Occupational therapists are needed to meet the health and occupational needs of the global population, but we know little about the type of findings generated by occupational therapy workforce research conducted worldwide. We aim to synthesize these findings and their range of content to inform future investigations. A scoping review with content analysis was used. Six scientific databases, websites of official institutions, snowballing, and key informants were used for searches. Two independent reviewers took… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…Our previous scoping review of the occupational therapy workforce research found no study explicitly addressing task shifting or task sharing strategies [22]; this is an important background nding to understand the accounts of some participants with their initial hesitancy toward the strategy. On the one hand, this may imply a lower familiarity with the scope and purpose of the strategy among occupational therapy representatives; this reinforces the need for added clarity, speci city, and contextualization of any related documentation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous scoping review of the occupational therapy workforce research found no study explicitly addressing task shifting or task sharing strategies [22]; this is an important background nding to understand the accounts of some participants with their initial hesitancy toward the strategy. On the one hand, this may imply a lower familiarity with the scope and purpose of the strategy among occupational therapy representatives; this reinforces the need for added clarity, speci city, and contextualization of any related documentation.…”
Section: Discussionmentioning
confidence: 99%
“…The mapping review found minimal yearly growth in research volume, with over-reliance on crosssectional studies, little use of advanced study methods, and few studies targeting LMICs [21]. Another review synthesized the ndings of occupational therapy workforce research to determine many important topics were minimally-addressed (e.g., racial/ethnic workforce representation) or not addressed at all (e.g., situational analyses, task shifting) [22]. A synthesis of study limitations and recommendations concluded that longitudinal studies were needed, in addition to strengthening of routine workforce data collection [14].…”
Section: Introductionmentioning
confidence: 99%
“…The World Federation of Occupational Therapists (WFOT) has recorded shortages in 62 countries and territories, equating to 65% of WFOT member countries/territories worldwide (WFOT, 2022). Evidence suggests that more research is needed to fully understand and address occupational therapy workforce challenges globally, noting that existing research is scarce, inequitably distributed, poorly funded and of limited quality, especially in comparison to workforce research on other health professions (Jesus et al, 2023).…”
Section: How Do We Tackle the Challenge?mentioning
confidence: 99%
“…15 Within the context described, WFOT has led a research-based, multistage development process to launch the rst global strategy for strengthening this workforce. The process started with a multipronged scoping review of the occupational therapy workforce to synthesize: a) the scope and limited growth of this the research; 16 b) the types of ndings generated, including the topics remaining unaddressed across nations 17 and c) the reported limitations or recommendations regarding which workforce data and other improvements need to be made. 18 Based on an integrated synthesis of these ndings, a situational analysis was conducted that included the input of an advisory board with health workforce experts from within and outside the profession.…”
mentioning
confidence: 99%